2007
DOI: 10.1128/jb.00864-07
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium diphtheriae : Identification and Characterization of a Channel-Forming Protein in the Cell Wall

Abstract: The cell wall fraction of the gram-positive, nontoxic Corynebacterium diphtheriae strain C8 r (؊) Tox ؊ ‫؍(‬ ATCC 11913) contained a channel-forming protein, as judged from reconstitution experiments with artificial lipid bilayer experiments. The channel-forming protein was present in detergent-treated cell walls and in extracts of whole cells obtained using organic solvents. The protein had an apparent molecular mass of about 66 kDa as determined on Tricine-containing sodium dodecyl sulfate-polyacrylamide gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 76 publications
2
25
1
3
Order By: Relevance
“…Participation of fragmentencoded polypeptides complementing the channel deficiency of the C. glutamicum ⌬porH ⌬porA mutant was studied by site-directed mutagenesis. Therefore, the TOPO 2.1 vector with the original PCR amplicon of strain ATCC 11913 (53) was subjected to QuikChange (QC) PCR using Pfu DNA polymerase (Fermentas) and QC primers in Table 2 (e.g., FP Cd_WTQC1/RP Cd_WTQC1) as described by the manufacturer. Amplicons that contained the intended mutations were cut from the TOPO 2.1 plasmid with EcoRI and XbaI and inserted into the backbone of pXMJ19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation of fragmentencoded polypeptides complementing the channel deficiency of the C. glutamicum ⌬porH ⌬porA mutant was studied by site-directed mutagenesis. Therefore, the TOPO 2.1 vector with the original PCR amplicon of strain ATCC 11913 (53) was subjected to QuikChange (QC) PCR using Pfu DNA polymerase (Fermentas) and QC primers in Table 2 (e.g., FP Cd_WTQC1/RP Cd_WTQC1) as described by the manufacturer. Amplicons that contained the intended mutations were cut from the TOPO 2.1 plasmid with EcoRI and XbaI and inserted into the backbone of pXMJ19.…”
Section: Methodsmentioning
confidence: 99%
“…The fragment complements the channel deficiency of the C. glutamicum ⌬porH ⌬porA mutant (53). Gene silencing disclosed that the 59-amino-acid small protein CdPorH, together with CdPorA, accounted for the channel activity.…”
Section: Fig 1 Orf Analyses Of a Plasmid-encoded C Diphtheriae Framentioning
confidence: 99%
“…They show in addition that the PorAPorH channel shares the characteristic fingerprints of channels such as bacterial porin (34) and also mitochondrial porin (35): closure at positive and negative potential with fast and slow kinetics, asymmetric voltage dependence, and multiple conductance states. Similar porin channels can be found in related families of bacteria, C. diphtheria, C. efficiens, and N. farcinia (8,36,37).…”
Section: Purification Of C Glutamicum and Cf-expressed Proteins-mentioning
confidence: 87%
“…In this study, we identified a channel from the cell wall of D. maris DSM 43672. A protein responsible for channel formation was identified with a molecular mass of about 120 kDa, which may be formed from a homooligomer of smaller polypeptides similar to the situation in other members of mycolata, where the cell wall channels are frequently formed by oligomers [18][19][20][21]. According to results of the lipid bilayer conductance measurements, the cell wall channel of D. maris DSM 43672 is wide, water filled and has a high preference for the passage of cations.…”
Section: Introductionmentioning
confidence: 97%
“…This means that the mycolic acid layer has the same function as the outer membranes of Gram-negative bacteria, which contain porins for the passage of hydrophilic solutes. Accordingly, channel-forming proteins with characteristics similar to the porins of their Gram-negative counterparts have been identified as existing in the cell walls of multiple members of the mycolata, including Mycobacterium chelonae and Mycobacterium bovis [15,16], Nocardia farcinica [17,18], Corynebacterium diphtheriae, Corynebacterium glutamicum, Corynebacterium amycolatum [19][20][21][22][23], Rhodococcus equi and Rhodococcus erythropolis [24,25]. It is therefore likely that channel-forming proteins are widely distributed in the mycolata and are responsible for the uptake of hydrophilic compounds across the mycolic acid layer.…”
Section: Introductionmentioning
confidence: 99%